The art of M&A : - Reed, Stanley Foster (McGraw-Hill, 2007)
Authoritative and completely up-to-date, the Fourth Edition of The Art of M&A is an unsurpassed, one-stop guide to every facet of mergers and acquisitions that enables you to make winning deals with complete confidence. This definitive resource retains its popular Q&A format, offering quick access to all the changes that have occurred in the field since the merger wave of the 1990s. The book explores every key aspect of winning M&A transactions, and presents advice on avoiding common M&A pitfalls.